Analisis Kebijakan Penanggulangan Kemiskinan Petani Di Indonesia Untuk Mewujudkan Keadilan Pertanian - Arifah, Kuni Nasihatun; Novita, Diana; Sunarso, Hendro (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2023)
Farmer poverty in Indonesia is a complex problem that requires serious attention in efforts to achieve agricultural sustainability and inclusive national development. This research aims to provide a comprehensive policy analysis related to reducing farmer poverty with a focus on achieving justice in the agricultural sector.This study includes identifying poverty problems experienced by farmers in Indonesia, with an emphasis on access to key resources such as land, water and credit. Furthermore, this research evaluates the impact of fluctuations in agricultural commodity prices on farmers' income and analyzes existing policies in order to reduce inequality in agriculture.The research results show that agricultural problems in rural areas are caused by many things, namely lack of access to land and also technological backwardness in rural agriculture. This problem has a big impact on poverty rates in rural areas, where the majority of 80 percent of Indonesia's population are farmers